Automation system for Dr. Rosli Clinic / Hishamudin Alli...[et al.] - Alli, Hishamudin; Mohd Yusof, Jamilah Wardah; Udin, Mohd Zin; Abd. Aziz, Jamiilah (1990)
Klinik Dr. Rosli is a private clinic which operates under the jurisdiction of the Ministry of Health, Akta Perubatan 1971 and Malaysian Medical Association. This clinic was opened in June, 1987 and provide a general services. Dr. Rosli has one clinic registered under sole proprietorship as Klinik Dr. Rosli - Klinik Kanak- kanak dan Dewasa and it is located at 108, Blok 15, Jalan 18.3, Section 18, Shah Alam. The principal function of the clinic is to provide quality medical services at reasonable costs in line with the medical code of ethic. It provides general outpatient treatment for adults and children. It is currently serving an approximately 20 patients per day of which 40% consist of cash patients and 60% from billed patients from a list of 12 corporates and semi-government sponsored patients.